Polyimide-containing aqueous dispersions and methods for producing same

By adding polyamic acid, amino, propylene glycol monomethyl ether and lignin to the water-based polyimide-fluororesin dispersion, high-performance coatings without using organic solvents are prepared, which solves the problems of safety and dispersion complexity and realizes environmentally friendly and efficient coating applications.

JP7626422B2Active Publication Date: 2025-02-04JAPAN MATEX CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020155575
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-16
Publication Date
2025-02-04
Estimated Expiration
2040-09-16

AI Technical Summary

Technical Problem

The use of organic solvents in the preparation process of existing water-based polyimide and fluororesin dispersions leads to safety and environmental impact problems, and the dispersion complexity and cost are high, making it difficult to meet the needs of industrial applications.

Method used

Using a mixed dispersion of water-based polyimide-fluororesin without organic solvents, polyamic acid, amino, propylene glycol monomethyl ether and lignin are added, and uniform dispersion is achieved by adjusting the pH value and particle treatment to prepare high-performance coatings.

Benefits of technology

It provides safe, environmentally friendly and efficient coating solutions, with excellent adhesion, heat resistance and corrosion resistance, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626422000013
    Figure 0007626422000013
  • Figure 0007626422000014
    Figure 0007626422000014
  • Figure 0007626422000015
    Figure 0007626422000015
Patent Text Reader

Abstract

To provide a paint, a coating, or a sizing agent, composed of an aqueous mixture, having high-level adhesion, insulation, heat resistance (at 380-400°C), and corrosion resistance, without using organic solvent, and methods for producing the same.SOLUTION: A polyimide-based aqueous dispersion is based on a polyamide acid-containing PIA aqueous dispersion and includes active ingredients such as a lignin, so that it exhibits excellent handleability (e.g., safety, environmental load, cost of equipment) and excellent adhesion and heat resistance.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide-based aqueous dispersion and a method for producing the same, and more particularly to an aqueous dispersion based on a PIA aqueous dispersion containing polyamic acid (amic acid) and containing an active ingredient such as lignin, and a method for producing the same. [Background technology]

[0002] Polyimide-containing aqueous mixtures for paints and coating materials and methods for producing them have been known for some time. For example, aqueous mixtures for producing polyimide and fluororesins such as PTFE (polytetrafluoroethylene) are known, which are used for surface treatment of food industry products, kitchen utensils such as frying pans and pots, household products such as irons, electrical industry products, and mechanical industry products.

[0003] As such an aqueous mixture, for example, Patent Document 1 discloses a fluorine-based resin-containing polyimide precursor solution composition characterized by containing at least a non-aqueous dispersion of a fluorine-based resin that contains a fluorine-based resin micropowder and a fluorine-based additive containing at least a fluorine-containing group and a lipophilic group and has a water content of 5000 ppm or less as measured by the Karl Fischer method, and a polyimide precursor solution.

[0004] According to Patent Document 1, a polyimide precursor solution composition in which the dispersion state of the fluororesin is uniformly controlled, a polyimide obtained by this composition, which has excellent heat resistance, mechanical properties, sliding properties, insulating properties, electrical properties such as low dielectric constant and low dielectric loss tangent, and processability, a polyimide film, and a method for producing them, as well as circuit boards, coverlay films, insulating films, interlayer insulating films for wiring boards, surface protective layers, sliding layers, peeling layers, fibers, filter materials, electric wire coating materials, bearings, paints, heat insulating shafts, trays, various belts such as seamless belts, tapes, tubes, etc. are provided. However, the composition described in Patent Document 1 uses an organic solvent as a solvent to uniformly disperse the polyimide and the fluororesin, so there are problems with handleability (safety, environmental load, equipment costs, etc.). Therefore, there has been a demand for a mixed aqueous dispersion of polyimide and fluororesin that is excellent in handleability and does not use an organic solvent.

[0005] In order to solve such problems of the conventional technology, the present inventors attempted to develop an aqueous polyimide-fluororesin mixed dispersion that has excellent adhesive properties and heat resistance without using an organic solvent. As a result, the present inventors completed an aqueous mixed dispersion containing polyimide, fluororesin, alumina, and potassium persulfate as such a dispersion, in which polyimide and fluororesin are uniformly dispersed, as well as a mixed powder produced from this dispersion, and a method for producing the same (Patent Application No. 2019-98015).

[0006] However, the above-mentioned mixed dispersion system is relatively complicated, and there is still room for improvement in terms of the complexity and cost involved in preparing the dispersion.

[0007] Meanwhile, as the development of industrial raw materials with less environmental impact is gaining attention, lignin as an industrial raw material is attracting attention. Lignin is one of the main components that make up plant cell walls along with cellulose and hemicellulose, and is an amorphous polymeric compound with aromatic rings. Industrially, lignin can be obtained as a denatured structure in the wastewater from pulp production. Lignin can be supplied in relatively large quantities in Japan, which is rich in forest resources (a rough estimate is that lignin accounts for 20-30% of the plant resources sustainably produced by local agriculture and forestry), and since it is a naturally derived phenolic resin, there was the possibility that it could be used as a substitute for phenolic resin, a regular industrial material. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2016-210886 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present inventors have been developing paints using a combination of a polyimide-based aqueous dispersion and lignin, but the performance was not necessarily satisfactory. However, by changing the polyimide and additives in the aqueous dispersion, we have found that it is possible to provide paints, coatings, and sizing agents made of aqueous mixtures with high levels of adhesion, insulation, heat resistance, and corrosion resistance, and methods for producing the same. [Means for solving the problem]

[0010] That is, the present inventors have found that a polyimide-based aqueous dispersion is based on an aqueous PIA dispersion containing polyamic acid, and by including an active ingredient such as lignin, it is possible to obtain an aqueous dispersion for use as a paint, coating, and sizing agent that exhibits excellent handleability (safety, environmental impact, equipment costs, etc.) as well as excellent adhesive performance and heat resistance, and have completed the present invention.

[0011] The invention according to claim 1 is for use as an agent selected from the group consisting of paints, varnishes, coating agents, and sizing agents. An aqueous dispersion comprising: , polyamic acid, amine, propylene glycol monomethyl ether , and lignin are dispersed therein, and the mixture is composed of 10 to 30% by weight of polyamic acid, 5 to 20% by weight of amine, and 5 to 20% by weight of propylene glycol monomethyl ether. The present invention relates to an aqueous dispersion containing

[0013] Claim 2 The present invention relates to a composition comprising 15 to 25% by weight of polyamic acid, 10 to 15% by weight of an amine, and 5 to 15% by weight of propylene glycol monomethyl ether. 1 The present invention relates to an aqueous dispersion according to the above.

[0015] Claim 3 The invention relates to a process for producing a lignin-based composition comprising 10 to 30% by weight of lignin. 1 or 2 The present invention relates to an aqueous dispersion according to the above.

[0016] Claim 4 The invention further comprises polyethylene glycol. Any one of items 1 to 3 The present invention relates to an aqueous dispersion according to the above.

[0017] Claim 5 The present invention relates to a method for producing a rubber composition comprising the steps of: (a) providing a rubber composition for producing a rubber sheet having a rubber base material and a rubber composition for producing a rubber base material, the rubber composition further comprising at least one selected from the group consisting of polytetrafluoroethylene (PTFE, tetrafluoroethylene), tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), epoxy, phenol, urethane, acrylic, FRP, and inorganic filler. 4 The present invention relates to an aqueous dispersion according to any one of the above items.

[0018] Claim 6 The invention relates to The above The inorganic filler is one or more fine particles selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal quartz (registered trademark), and the particle size of the inorganic filler is 3 μm or less. 5 The present invention relates to an aqueous dispersion according to the above.

[0019] Claim 7 The invention relates to The above The inorganic filler is treated with a silane coupling agent. 5 or 6 The present invention relates to an aqueous dispersion according to the above.

[0020] Claim 8 The present invention relates to a polyamic acid, an amine , P Propylene glycol monomethyl ether and lignin is dispersed therein, and the mixture contains 10 to 30% by weight of polyamic acid, 5 to 20% by weight of amine, and 5 to 20% by weight of propylene glycol monomethyl ether. A step of preparing an aqueous dispersion 1, and 1 An alkaline aqueous solution is added to the aqueous dispersion to adjust the pH of the aqueous dispersion. 8 The present invention relates to a method for producing an aqueous dispersion for use as an agent selected from the group consisting of paints, varnishes, coating agents, and sizing agents, the method comprising the step of adjusting the content of each component to 10.

[0021] Claim 9 The present invention relates to a process for preparing an aqueous dispersion 2 containing the inorganic filler, the process including, before the pH adjustment process, a process of crushing and sieving the inorganic filler to obtain polar crystalline fine particles having a particle size of 3 μm or less, and a process of preparing an aqueous dispersion 2 containing the inorganic filler. The process Include claims 8 The present invention relates to a method for producing the aqueous dispersion described above.

[0022] Claim 10 The invention relates to The above Claims: The inorganic filler is one or more selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal quartz. 9 The present invention relates to a method for producing the aqueous dispersion described above.

[0023] Claim 11 The invention relates to The above Claim 9: The inorganic filler is treated with a silane coupling agent. or 10 A method for producing the aqueous dispersion according to claim 1.

[0024] The invention according to claim 12 comprises claims 1 to 7 The present invention relates to a coating method, comprising a step of applying the aqueous dispersion according to any one of the above items to a coating surface. The invention according to claim 13 relates to the coating method according to claim 12, further comprising a step of heat-treating the coating surface onto which the aqueous dispersion has been applied at 350 to less than 500°C. Effect of the Invention

[0025] According to the invention of claim 1, a polyamic acid, an amine, and propylene glycol monomethyl ether are included. , and lignin are dispersed therein, and the mixture is composed of 10 to 30% by weight of polyamic acid, 5 to 20% by weight of amine, and 5 to 20% by weight of propylene glycol monomethyl ether. Since the aqueous dispersion contains the above-mentioned, it is possible to provide an aqueous mixed dispersion in which polyamic acid, an amine, and propylene glycol monomethyl ether are uniformly dispersed, for use as an agent selected from the group consisting of paints, varnishes, coating agents, and sizing agents. Furthermore, since the aqueous dispersion contains lignin, it can have better coatability. Therefore, it can be made into an aqueous dispersion for use as an agent selected from the group consisting of paints, coating agents, and sizing agents, having excellent coating properties without using organic solvents. In addition, since this aqueous dispersion does not contain an organic solvent, it has excellent handleability (safety, environmental load, equipment costs, etc.). Furthermore, this aqueous dispersion has It contains 10-30% by weight of polyamic acid, 5-20% by weight of amine, and 5-20% by weight of propylene glycol monomethyl ether. It can form a coating that has high-performance adhesive and bonding properties, as well as excellent heat resistance, insulation, radiation heat dissipation properties, and rust and corrosion resistance.

[0027] Claim 2 According to the present invention, the composition contains 15-25% by weight of polyamic acid, 10-15% by weight of amine, and 5-15% by weight of propylene glycol monomethyl ether, and therefore can be made into an aqueous dispersion for forming a coating film or coating having high-performance adhesive and tackiness functions, as well as excellent heat resistance, insulation properties, radiation heat dissipation properties, and rust and corrosion prevention properties.

[0029] Claim 3 According to the invention, since the aqueous dispersion contains 10 to 30% by weight of lignin, it is possible to provide an aqueous dispersion with superior coatability.

[0030] Claim 4According to the invention relating to the above, since the aqueous dispersion further contains polyethylene glycol, it is possible to obtain an aqueous dispersion having better coatability.

[0031] Claim 5 According to the invention, since the composition further contains at least one selected from the group consisting of polytetrafluoroethylene (PTFE, tetrafluoroethylene), tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), epoxy, phenol, urethane, acrylic, FRP, and inorganic filler, it is possible to provide a composition having superior heat resistance, processability, and moldability, as well as high adhesion and insulation properties.

[0032] Claim 6 According to the invention, the inorganic filler is one or more fine particles selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal quartz (registered trademark), and the particle size of the inorganic filler is 3 μm or less, so that a composition having superior heat resistance, processability, and moldability can be provided.

[0033] Claim 7 According to the invention relating to the above, since the inorganic filler is treated with a silane coupling agent, it is possible to provide a composition having superior heat resistance, processability, and moldability.

[0034] Claim 8 According to the present invention, a polyamic acid, an amine , P Propylene glycol monomethyl ether and lignin is dispersed therein, and the mixture contains 10 to 30% by weight of polyamic acid, 5 to 20% by weight of amine, and 5 to 20% by weight of propylene glycol monomethyl ether. A step of preparing an aqueous dispersion 1, and 1 Add an alkaline aqueous solution to the aqueous dispersion 1 pH of 8~The method for producing an aqueous dispersion for use as an agent selected from the group consisting of paints, varnishes, coating agents, and sizing agents, includes a step of adjusting the content of each component to 10, thereby making it possible to produce an aqueous dispersion having excellent dispersibility and excellent coating properties in an aqueous solution that does not contain an organic solvent and thus improving dispersibility in the aqueous solution that does not contain an organic solvent.

[0035] Claim 9 According to the invention, the pH adjustment step includes a step of crushing and sieving an inorganic filler to obtain polar crystalline fine particles having a particle size of 3 μm or less, and a step of preparing an aqueous dispersion 2 containing the inorganic filler. The process Since the polyimide-containing polymer contains the polyimide, the dispersibility in an aqueous solution not containing an organic solvent can be improved, and a polyimide-fluororesin-polar crystalline fine particle mixed aqueous dispersion having better dispersibility and better coating properties can be produced.

[0036] Claim 10 According to the invention, since the inorganic filler is one or more selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal sapphire (registered trademark), a mixed aqueous dispersion having better coating properties can be produced.

[0037] Claim 11 According to the present invention, since the inorganic filler is treated with a silane coupling agent, a mixed aqueous dispersion having better coating properties can be produced.

[0038] Claim 12 According to the invention, claims 1 to 7 Since the method includes a step of applying the aqueous dispersion described in any one of claims 1 to a coating surface, it is possible to form a coating film or coating that also has excellent heat resistance, insulating properties, radiation heat dissipation properties, and rust and corrosion prevention properties. [Brief description of the drawings]

[0039] [Figure 1]FIG. 2 is an explanatory diagram showing the results of a heat resistance test of a coating film (thickness: 3 μm) prepared using the aqueous dispersion of the present invention containing propylene glycol monomethyl ether (PM). [Diagram 2] FIG. 2 is an explanatory diagram showing the results of a heat resistance test of a coating film (thickness: 6 μm) prepared using the aqueous dispersion of the present invention containing PM. [Diagram 3] FIG. 2 is an explanatory diagram showing the results of a heat resistance test of a coating film (thickness: 6 μm) produced using the aqueous dispersion of the present invention containing PM, PTFE, and an alumina filler. [Figure 4] FIG. 2 is an explanatory diagram showing the results of a heat resistance test of a coating film (thickness: 11 μm) produced using the aqueous dispersion of the present invention containing PM, PTFE, and an alumina filler. [Diagram 5] FIG. 1 is an explanatory diagram showing the results of a boiling water resistance test for coating films (thicknesses 6 μm and 11 μm) prepared using the aqueous dispersion of the present invention containing PM and PTFE, and coating films (thicknesses 5 μm and 9 μm) prepared using tourmaline in addition to PM and PTFE. [Figure 6] FIG. 1 is an explanatory diagram showing the results of a boiling water resistance test for coating films (thicknesses of 7 μm and 14 μm) prepared using the aqueous dispersion of the present invention containing PM and cresol novolac epoxy resin emulsion, and coating films (thicknesses of 7 μm and 14 μm) prepared using tourmaline in addition to PM and cresol novolac epoxy resin emulsion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] Hereinafter, preferred embodiments of the aqueous dispersion containing polyamic acid, an amine, and propylene glycol monomethyl ether for use as an agent selected from the group consisting of paints, coating agents, and sizing agents according to the present invention will be described.

[0041] The water used in the aqueous dispersion of the present invention is ion-exchanged water. For the aqueous dispersion of the present invention to exhibit its function, the electrical interaction of the components is important. Therefore, in the present invention, ion-exchanged water is preferably used, and tap water is basically not used.

[0042] The dispersion may be a mixed aqueous dispersion, which includes a polyamic acid, an amine, and propylene glycol monomethyl ether.

[0043] Polyamic acid, also known as amic acid, is known as a precursor of polyimide, which is widely used as a chemical material. Recently, polyamic acid has been obtained industrially by decomposing waste polyimide and used as a raw material for synthesizing new polyimide (Patent No. 6402283, Patent No. 6487501, Patent No. 6186171, etc.).

[0044] Polyimide (PI) is a resin made of a polymer that has imide bonds in its molecular structure. Polyimide can be synthesized, for example, by the general synthesis method shown in the following formula. In this synthesis method, equimolar amounts of tetracarboxylic dianhydride and diamine are polymerized as raw materials to obtain polyamic acid, which is a precursor of polyimide.

[0045] [ka] This polyamic acid is heated to 200°C or higher, or a catalyst is used to promote a dehydration and cyclization (imidization) reaction to obtain polyimide. When a catalyst is used, amine compounds are often used, and a carboxylic acid anhydride may also be used in combination as a dehydrating agent to quickly remove the water generated by the imidization.

[0046] [ka]

[0047] In this specification, a compound that can be a raw material for polyimide is called a polyimide precursor. The polyimide precursor includes polyamic acid. The polyimide precursor may also include a substance described in Japanese Patent No. 5695675 or No. 6186171. The polyimide precursor is, for example, as shown below.

[0048] [ka]

[0049] [ka] (In the formula, the symbol X is an alkali metal (lithium / Li, sodium / Na, potassium / K, rubidium / Rb, or cesium / Ce), the subscripts n and l are symbols indicating the amount (number of moles) of polyamic acid structures present on both sides of the polyimide structure, and are usually values ​​within a range of 0.1 to 0.8, and the subscript m is a symbol indicating the amount (number of moles) of polyimide structures present, and are usually values ​​within a range of 0.2 to 0.9.)

[0050] The polyimide is not particularly limited, and examples thereof include resins made of high molecular weight polymers obtained by the reaction of aromatic tetracarboxylic anhydrides such as pyromellitic anhydride, and any polyimide that is obvious to a person skilled in the art can be used. The polyimide may be recycled polyimide obtained by crushing used polyimide, or may be unused polyimide. The shape of the polyimide is not particularly limited, but from the viewpoint of being able to easily maintain a suspended and dispersed state in the mixed aqueous dispersion for a long period of time, it is desirable for the polyimide to be fine particles with a particle size in the range of 1 μm to 100 μm. The content of the polyimide is preferably 10% by weight to 40% by weight, and more preferably 15% by weight to 30% by weight, based on the mixed aqueous dispersion.

[0051] The aqueous dispersion of the present invention contains polyamic acid, which is a precursor of polyimide. Polyamic acid can be dehydrated and cyclized (imidized) by heating at 160° C. or higher. This imidization process allows the polyamic acid-containing mixed aqueous dispersion to form a stronger coating.

[0052] Furthermore, the aqueous dispersion of the present invention may contain one or more polyimide analogues selected from polyamic acid or polyamide ester as polyimide precursors. These polyimide analogues have a positive effect on the adhesive performance of the mixed aqueous dispersion and are essential components for producing a coating film with high heat resistance and high strength. Preferably, the mixed aqueous dispersion of the present invention contains a polyimide dispersion containing polyamic acid.

[0053] Examples of preparations containing polyimide as a raw material that are preferably used in the present invention include W-20 manufactured by Nakada Coating Co., Ltd., but are not limited thereto.

[0054] Such formulations may also contain phosphoric acid, ethanol dispersions, amines, propylene glycol, nonionic components (neutral additives), carbon black as a coloring component, and the like.

[0055] The amount of polyamic acid contained in the aqueous dispersion of the present invention is 1 to 50% by weight, 5 to 40% by weight, or 10 to 30% by weight, preferably 10 to 30% by weight, based on the total weight of the aqueous dispersion. By containing 10 to 30% by weight of polyamic acid, the aqueous dispersion can have better coatability.

[0056] The term "amine" as used herein has the meaning normally understood by those skilled in the art, i.e., amine is a general term for compounds in which the hydrogen atom of ammonia is replaced with a hydrocarbon group or an aromatic atomic group. If the number of replacements is one, it is called a primary amine, if the number of replacements is two, it is called a secondary amine, and if the number of replacements is three, it is called a tertiary amine. In addition, an alkyl group is bonded to a tertiary amine to form a quaternary ammonium cation. Ammonia also belongs to the amine category. Amines used in the present invention include, but are not limited to, methyldiethanolamine (MDEA). While chemically, they are widely used as bases and ligands, industrial applications include use as synthesis catalysts in electronics-related products, integrated circuits, liquid crystal displays, semiconductor-related products, raw materials for electronic devices, and polymer and resin additives. In addition, here, electronic devices are a general term for elements that apply the function of electrons to perform active work such as amplification.

[0057] The amount of amine contained in the aqueous dispersion of the present invention is 1 to 50% by weight, 2 to 30% by weight, or 5 to 20% by weight, preferably 5 to 20% by weight, based on the total weight of the aqueous dispersion. Amine By containing the above, it is possible to provide an aqueous dispersion having better coatability.

[0058] As used herein, the term "propylene glycol monomethyl ether" has the meaning commonly understood by those skilled in the art, i.e., a compound having the following chemical formula (C4H10O2) and a molecular weight of 90.12, also known as 1-methoxy-2-propanol. Propylene glycol monomethyl ether is used in applications such as low toxicity solvents, ink solvents, flux cleaners for electronic materials, copying fluids, substitutes for glycol-based solvents, industrial detergents, and adhesive solvents.

[0059] [ka]

[0060] The amount of propylene glycol monomethyl ether contained in the aqueous dispersion of the present invention is 1 to 50% by weight, 2 to 30% by weight, or 5 to 20% by weight, preferably 5 to 20% by weight, based on the total weight of the aqueous dispersion. Propylene glycol monomethyl ether By containing the above, it is possible to provide an aqueous dispersion having better coatability.

[0061] The aqueous dispersion of the present invention may contain lignin. Lignin is a phenolic polymer that is one of the main components of wood and plays a role in bonding fibers in wood together. That is, it is a polymeric phenolic compound involved in lignification of higher plants. Lignin is a giant biopolymer in which three types of lignin monomers (monolignols), p-coumaryl alcohol (p-hydroxycinnamyl alcohol), coniferyl alcohol, and sinapyl alcohol, are one-electron oxidized under the catalyst of enzymes (laccase and peroxidase) to form phenoxy radicals, which are then highly polymerized by random radical coupling to form a three-dimensional network structure.

[0062] Lignin is one of the main components of wood, but when exposed to sunlight (ultraviolet rays), it turns brown. Therefore, when producing pulp from wood, it is essential to remove lignin from wood chips depending on the quality of paper required. Thus, a large amount of lignin is generated as waste in the paper production process, and methods for industrially utilizing this lignin have been sought. Since lignin can be said to be a naturally occurring phenolic resin, it may be used as an alternative raw material to synthetic phenolic resins. The present inventors have focused on the possibility of using lignin as a raw material for an aqueous dispersion to be used as an agent selected from the group consisting of paints, coating agents, and sizing agents.

[0063] The lignin in the present invention is used as a substitute for resin in the aqueous coating composition, so the amount of the lignin used is not particularly limited, but is 1 to 50% by weight, 5 to 40% by weight, or 10 to 30% by weight of the entire aqueous dispersion, and 10 to 30% by weight is particularly preferred. By including 10 to 30% by weight of lignin, an aqueous dispersion with better coatability can be obtained.

[0064] The aqueous dispersion of the present invention may further contain at least one selected from the group consisting of polytetrafluoroethylene (PTFE), epoxy, phenol, urethane, acrylic, FRP, and inorganic filler. In this specification, the terms "polytetrafluoroethylene (PTFE)," "epoxy," "phenol," "urethane," "acrylic," "FRP," and "inorganic filler" have the meanings commonly understood by those skilled in the art.

[0065] "Polytetrafluoroethylene (PTFE, tetrafluoroethylene)" is a polymer of tetrafluoroethylene, a fluororesin (fluorocarbon resin) consisting only of fluorine atoms and carbon atoms. It is known by the trade name Teflon (registered trademark). It is chemically stable and has excellent heat and chemical resistance, and is widely used as a processing material in chemical and mechanical applications involving electrical connections and high-temperature corrosive fluids. In addition, "tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA)" and "tetrafluoroethylene-hexafluoropropylene copolymer (FEP)" have similar properties to PTFE and are used for similar applications.

[0066] The term "epoxy" here means "epoxy resin", which is a general term for thermosetting resins that can be crosslinked and networked with epoxy groups remaining in the polymer. Epoxy resins have a heat resistance of 80°C and a cold resistance of -30°C, and are easy to handle because of their low toxicity and flammability.

[0067] The term "phenol" here means "phenolic resin", which is one of the thermosetting resins made from phenol and formaldehyde, and is the first resin in the world to be artificially synthesized from raw materials other than plants. The aforementioned lignin is a natural phenolic resin. Phenolic resin has the characteristics of heat resistance of 150 to 180°C, high adhesiveness, strong acid resistance, and high electrical insulation.

[0068] The aqueous dispersion of the present invention may contain an inorganic filler. The inorganic filler is preferably a fine particle derived from any mineral having at least some electrical properties. More preferably, the inorganic filler is a polar crystalline body. In this specification, a polar crystalline body refers to a crystalline body having a positive electrode (+) on one side and a negative electrode (-) on the opposite side. A polar crystalline body is always in an unstable state (electric potential difference), and due to this electric potential difference, electrons are constantly emitted and flow from the negative electrode to the positive electrode. In this specification, the polar crystalline body fine particle is one or more selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal stone (registered trademark), but is not limited to these.

[0069] One of the best known polar crystals is tourmaline, which has the chemical formula XY3Al6(BO3)3SiO 18 It is a crystal composed of (O,OH,F)4, of which dravite (magnesium oxide) NaMg3Al6(BO3)3Si6O 18 (OH)4, elbaite (sphaerite) Na(Li,Al)3Al6(BO3)3Si6O 18 (OH)4, Schorl (iron tourmaline) NaFe3Al6(BO3)3Si6O 18 (OH)4, uviteCaMg3(Al5Mg)(BO3)3Si6O 18 (OH,F)4 is what is called tourmaline.

[0070] Tourmaline is said to have been excavated in Ceylon, Sri Lanka, in 1703 and brought to Europe. Later, in 1880, Pierre Curie, who was awarded the Nobel Prize in Physics, discovered that when tourmaline crystals are subjected to external pressure, an electric charge is generated on the crystal surface. It was also discovered that an electric charge is generated when thermal energy is applied to tourmaline. The phenomenon that occurs when pressure is applied to tourmaline is called piezoelectricity, and when heat is applied, electrons are separated at both poles of the crystal, generating positive and negative electricity, called pyroelectricity. When pressure or heat is applied to tourmaline, positive and negative electrodes are generated at both poles of the stone, generating electricity. The positive pole attracts electrons, and the negative pole releases electrons outside the crystal (in water, on the surface of the skin, and other places where electricity flows easily). The water generated and the moisture in the air are electrolyzed to generate hydroxyl ions (H3O 2- ) which releases negative ions.

[0071] By using polar crystals, the present invention can obtain coating agents and paints with excellent coating properties, which is presumably due to the above-mentioned electrical properties of tourmaline, but is not limited to this.

[0072] Hexacite (registered trademark) may be used as the polar crystal. Hexacite (registered trademark) is a tuffaceous basalt consisting of rectangular plagioclase and clinopyroxene, opaque minerals, small amounts of olivine, and spherical or amorphous celadonite filling the spaces between them, and is a mineral that is distributed around the so-called amethyst in the surrounding rocks. As for the components, it is preferable that the Fe2O3 content is 5% or more by weight, and particularly 7% or more by weight.

[0073] In the present invention, inorganic fillers treated with a silane coupling agent may be used as the inorganic filler. Examples of silane coupling agents include vinyl trimethoxysilane, vinyl triethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-glycidoxypropyl triethoxysilane, p-styryl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxysilane, N-2- (aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and 3-trimethoxysilylpropylsuccinic anhydride may be mentioned, but are not limited to these.

[0074] In addition to the above-mentioned components, the mixed aqueous dispersion may contain other additives to modify the mixed aqueous dispersion. Examples of additives include, but are not limited to, solvents, tackifiers, plasticizers, curing agents, crosslinking agents, diluents, fillers, thickeners, pigments, etc., and any additives that are commonly used to modify the properties of the mixed aqueous dispersion and that are obvious to those skilled in the art can be used.

[0075] Hereinafter, a method for producing an aqueous dispersion containing a polyamic acid, an amine, and propylene glycol monomethyl ether for use as an agent selected from the group consisting of paints, coating agents, and sizing agents will be described.

[0076] The method for producing the aqueous dispersion includes the steps of preparing an aqueous dispersion 1 containing a polyamic acid, an amine, and propylene glycol monomethyl ether, and adding an alkaline aqueous solution to the aqueous dispersion to adjust the pH of the aqueous dispersion to about 10.

[0077] The method for producing this aqueous dispersion may further include, before the pH adjustment step, a step of crushing and sieving the inorganic filler to obtain polar crystalline fine particles having a particle size of 3 μm or less, a step of preparing aqueous dispersion 2 containing the inorganic filler, and a step of heat treating the aqueous dispersion at 350 to less than 500°C.

[0078] Polyimide may be difficult to dissolve in an aqueous solvent, and therefore, in order to improve the water dispersibility of the polyimide, the polyimide may be pretreated before preparing the mixed aqueous dispersion. The pretreatment step involves mixing polyimide with an ethanol solution of phosphoric acid, and then drying the mixture to evaporate the water, producing a polyimide-phosphoric acid mixed powder. By using the polyimide-phosphoric acid mixed powder, the water dispersibility of the polyimide can be greatly improved compared to the case where polyimide alone is used, and the mixed aqueous dispersion according to the present invention can be produced more easily. It goes without saying that the mixed aqueous dispersion according to the present invention can be produced without carrying out this pretreatment step.

[0079] The prepared aqueous dispersion can be converted into a powder by evaporating the water. The above powder has a uniform polyimide mixture and has excellent adhesiveness and heat resistance, and therefore can be used as an excellent molding material that can be used for a wide range of products, such as high heat resistant products.

[0080] The above powder is produced by drying an aqueous dispersion containing the polyamic acid, amine, and propylene glycol monomethyl ether according to the present invention to evaporate water. The drying method for producing the above powder is not particularly limited, and any method may be used as long as it can evaporate the water content of the aqueous dispersion according to the present invention to produce a powder.

[0081] The coating method using the aqueous dispersion of the present invention includes a step of applying the above-mentioned aqueous dispersion to a coating surface, and a step of heat-treating the surface to a temperature of 350 to less than 500°C. The heat treatment, also called baking, is a necessary step for producing the coating of the present invention, but the method of the heat treatment is not particularly limited, and any heating device commonly used in the art can be used.

[0082] The coating method using the aqueous dispersion of the present invention is usually intended for coating films or coatings on hard surfaces such as metal surfaces, but can also be applied to soft surfaces such as thin films and tapes, and extremely thin films, etc. In particular, coatings made from the aqueous dispersion of the present invention are effective for tapes and films that require insulation and heat resistance. EXAMPLES

[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0084] (Preparation of base material mixture) 20 wt % PIA powder, 12 wt % amine, 10 wt % propylene glycol monomethyl ether, and 58 wt % ion-exchanged water were mixed, and the pH was adjusted to 10 by adding an appropriate amount of amine.

[0085] (Preparation of lignin liquid) 20 wt% lignin powder (modified lignin, containing PEG), 20 wt% propylene glycol monomethyl ether, 13 wt% amine, and 47 wt% ion-exchanged water were mixed, and the pH was adjusted to 10 by adding an appropriate amount of amine.

[0086] Example 1: Lignin hybrid paint formulation A lignin hybrid paint was formulated by mixing 30 wt% of the base material mixture and 70 wt% of the lignin liquid.

[0087] (Example 2: Formulation of PTFE hybrid paint) A PTFE hybrid paint was formulated by mixing 30 wt% of the base material mixture and 70 wt% of the PTFE dispersion (water 40 wt%, solid content 60 wt%).

[0088] (Example 3: Formulation of epoxy hybrid paint) An epoxy hybrid paint was formulated by mixing 49 wt% of the base material mixture and 51 wt% of cresol novolac epoxy resin emulsion (solid content 45 wt%).

[0089] (Performance evaluation test 1 - Grid test) (Test Method) The cross-cut test was carried out as follows. 1. The compositions of the examples and comparative examples were each stirred in a thermostatic shaker at 60° C. for 2 hours. 2. The stirred Examples and Comparative Examples were applied to 2 mm thick aluminum plates (n=2 for each) using a bar coater to prepare samples. 3. The samples were baked at 380°C for 15-20 minutes. 4. The fired samples were subjected to a cross-cut test (cross-cut method) as specified in JIS K5600 5-6.

[0090] (Test Results) The results of the cross-cut adhesion test showed that the comparative examples only had the adhesive performance of conventional coatings, whereas the examples containing lignin, PTFE resin, or epoxy resin showed stronger adhesiveness than the comparative examples.

[0091] (Performance evaluation test 2 - Cloth tape peeling test (tape peeling test)) (Tape peeling test) The cross-cut test was carried out as follows. 1. The examples and comparative examples were each stirred in a thermostatic shaker at 60°C for 2 hours. A cloth tape (1 cm x 10 cm) was attached along the entire length of an aluminum plate (n = 2 for each) measuring 2.50 mm x 100 mm x 2 mm. The entire length of the cloth tape was longer than the entire length of the aluminum plate. This aluminum plate was used as a test piece. The mixed Examples and Comparative Examples were applied using a bar coater from the top of the cloth tape to halfway along the length of the test piece. 3. The coated surface of the test piece was baked at 380°C for 15 to 20 minutes. 4. A PTFE dispersion (60% solids, 40% water) was applied as a top coat to the entire test piece (thickness 35 μm to 60 μm) and then dried. 5. For each dried test piece, the cloth tape was pulled upward and peeled off from the side with only the top coat, and the degree to which the cloth tape peeled off from the border between the part with only the top coat and the part where the example or comparative example was applied was evaluated.

[0092] (Test Results) The results of the tape peel test showed that the comparative examples only had the adhesive performance of conventional coatings, whereas the examples containing lignin, PTFE resin, or epoxy resin showed stronger adhesiveness than the comparative examples.

[0093] The performance of the coatings according to the aqueous mixtures of the present invention is summarized in Table 1 below.

[0094] [Table 1]

[0095] (Performance evaluation test 3 - Coating heat resistance test) (procedure) The coating heat resistance test was carried out as follows. 1. The aqueous dispersions of the present invention were each stirred in a thermostatic shaker at 60°C for 2 hours. 2. The stirred aqueous dispersion of the present invention was applied to a 2 mm thick pure aluminum plate using a #14 bar coater to a film thickness of 3 μm or 6 μm to prepare a sample. 3. The samples were each fired under the following conditions: (1) 60 to 420°C for 45 minutes (2) 150 to 440°C for 45 minutes (3) 150 to 460°C for 58 minutes (4) 60 to 500°C for 75 minutes 4. While the temperature was rising to the target temperature, curing was also carried out at the same time. Once the target temperature was reached, the specimen was removed and rapidly cooled, after which an appearance evaluation and tape peeling test were performed. (Test Results) The coating heat resistance of the comparative example was below 420°C, but the coating heat resistance of the aqueous dispersion of the example (with silane coupling agent) was visually limited to 460°C, and the adhesion was limited to 420°C. This tendency was similar for coating thicknesses of 3 μm and 6 μm. Furthermore, in the example with PTFE / alumina filler, the coating heat resistance was visually limited to 480°C, and the adhesion was limited to 480°C. This tendency was similar for coating thicknesses of 6 μm and 11 μm.

[0096] (Performance evaluation test 4 - Boiling water resistance test after painting) (procedure) The boiling water resistance test after painting was carried out as follows. 1. The aqueous dispersions of the present invention were each stirred in a thermostatic shaker at 60°C for 2 hours. 2. The stirred aqueous dispersion of the present invention was applied to a 2 mm thick pure aluminum plate using a #14, 28 bar coater to give a film thickness of 5 μm, 6 μm, 9 μm or 11 μm to prepare samples. 3. The cured sample was placed in a pot of boiling water under the following conditions and left for 120 minutes, after which the appearance and adhesion were evaluated by tape peeling. (Test Results) The aqueous dispersion of the present invention containing PTFE and the original aqueous dispersion containing PTFE and epoxy passed the boiling water resistance test under the above effect conditions.

[0097] (Detailed explanation of the test results shown in the drawings) Below, details of the experiments shown in Figures 1 to 6 are given in Tables 2 to 7, respectively. Figure 1 shows the results of a heat resistance test of a coating film (thickness 3 μm) prepared using the aqueous dispersion of the present invention containing propylene glycol monomethyl ether (PM). Details of the test in Figure 1 are shown in Table 2. The heat resistance of this paint reached its limit at around 440°C, and at temperatures higher than this, deterioration or loss of the resin was observed, making it unusable as a coating film.

[0098] [Table 2]

[0099] Figure 2 shows the results of a heat resistance test of a coating film (6 μm thick) prepared using the aqueous dispersion of the present invention containing PM. Details of the test in Figure 2 are shown in Table 3. The heat resistance of this paint reached its limit at around 440°C, and at temperatures higher than this, deterioration or loss of the resin was observed, making it unusable as a coating film.

[0100] [Table 3]

[0101] Figure 3 shows the results of a heat resistance test of a coating film (6 μm thick) made using the aqueous dispersion of the present invention containing PM, PTFE, and alumina filler. The details of the test in Figure 3 are shown in Table 4. The heat resistance of this paint was good even at 460°C, but some problems were found at 480°C, and resin deterioration or peeling was observed at 500°C, making it unusable as a coating film.

[0102] [Table 4]

[0103] Figure 4 shows the results of a heat resistance test of a coating (11 μm thick) made using the aqueous dispersion of the present invention containing PM, PTFE, and alumina filler. The details of the test in Figure 4 are shown in Table 5. The heat resistance of this paint was good even at 460°C, but some problems were found at 480°C, and resin deterioration or peeling was observed at 500°C.

[0104] [Table 5]

[0105] Figure 5 shows the results of a boiling water resistance test of coatings (thicknesses 6 μm and 11 μm) made using the aqueous dispersion of the present invention containing PM and PTFE. The details of the test of Figure 5 are shown in Table 6. The coating performed very well in the boiling water resistance test.

[0106] [Table 6]

[0107] FIG. 6 is an explanatory diagram showing the results of a boiling water resistance test of coatings (7 μm and 14 μm thick) prepared using the aqueous dispersion of the present invention containing PM and cresol novolac epoxy resin emulsion. The details of the test in FIG. 6 are shown in Table 7. The coatings performed very well in the boiling water resistance test.

[0108] [Table 7] [Industrial Applicability]

[0109] The aqueous dispersion according to the present invention contains polyamic acid, an amine, and propylene glycol monomethyl ether, and therefore can be used as an agent selected from the group consisting of paints, coating agents, and sizing agents, which exhibit excellent adhesive performance and heat resistance, and such an aqueous dispersion can be produced by a simple operation. Furthermore, since the composition does not contain an organic solvent, it has excellent ease of handling (safety, environmental impact, equipment costs, etc.). Therefore, the polyimide-containing aqueous dispersion according to the present invention is suitable for use as a heat-resistant paint for pots, kettles, frying pans, etc., a heat-resistant impregnation agent for knitted fabrics, woven fabrics, glass fabric materials, carbon fibers, carbonized fibers, etc., and a coating agent, paint, varnish, etc. for various other products. In particular, the polyimide-containing aqueous dispersion according to the present invention is suitable for use in the manufacturing process of electric vehicles (EVs) and 5G (large-capacity, high-speed communication) devices due to its high heat resistance, high insulation properties, and high adhesion properties.

Claims

1. 1. An aqueous dispersion for use as an agent selected from the group consisting of paints, varnishes, coatings, and sizing agents, the dispersion comprising a polyamic acid, an amine, propylene glycol monomethyl ether, and lignin; An aqueous dispersion containing 10-30% by weight of a polyamic acid, 5-20% by weight of an amine, and 5-20% by weight of propylene glycol monomethyl ether.

2. 10. The aqueous dispersion of claim 1 comprising 15 to 25 weight percent polyamic acid, 10 to 15 weight percent amine, and 5 to 15% propylene glycol monomethyl ether.

3. 3. The aqueous dispersion of claim 1, comprising 10 to 30% by weight of lignin.

4. The aqueous dispersion according to any one of claims 1 to 3, further comprising polyethylene glycol.

5. The aqueous dispersion described in any one of claims 1 to 4, further containing at least one selected from the group consisting of polytetrafluoroethylene (PTFE, tetrafluoroethylene), tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), epoxy, phenol, urethane, acrylic, FRP, and inorganic filler.

6. The aqueous dispersion described in claim 5, wherein the inorganic filler is one or more types of fine particles selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal sapphire (registered trademark), and the particle size of the inorganic filler is 3 μm or less.

7. The aqueous dispersion of claim 5 or 6, wherein the inorganic filler is treated with a silane coupling agent.

8. preparing an aqueous dispersion 1 in which polyamic acid, an amine, propylene glycol monomethyl ether, and lignin are dispersed, the aqueous dispersion 1 containing 10 to 30% by weight of polyamic acid, 5 to 20% by weight of amine, and 5 to 20% by weight of propylene glycol monomethyl ether; A step of adding an alkaline aqueous solution to the aqueous dispersion 1 to adjust the pH of the aqueous dispersion 1 to 8 to 10.

1. A method for producing an aqueous dispersion for use as an agent selected from the group consisting of paints, varnishes, coatings, and sizing agents, comprising:

9. Before the pH adjustment step, the inorganic filler is crushed and sieved to obtain polar crystalline fine particles having a particle size of 3 μm or less; and A step of preparing an aqueous dispersion 2 containing the inorganic filler A method for producing the aqueous dispersion of claim 8, comprising:

10. A method for producing an aqueous dispersion as described in claim 9, wherein the inorganic filler is one or more selected from the group consisting of pink tourmaline, black tourmaline, and hexagonal sintered stone (registered trademark).

11. A method for producing an aqueous dispersion described in claim 9 or 10, wherein the inorganic filler is treated with a silane coupling agent.

12. A step of applying the aqueous dispersion according to any one of claims 1 to 7 to a coating surface. A coating method comprising:

13. The coating method according to claim 12, further comprising a step of heat treating the coating surface to which the aqueous dispersion has been applied at a temperature of 350 to less than 500°C.

Citation Information

Patent Citations

  • Aqueous dispersion and its production

    JP1999060947A

  • Fluorine-based resin-containing polyimide precursor solution composition, polyimide and polyimide film using the same, and methods for producing them

    JP2016210886A

  • PAI-based coating compositions

    JP2019521212A

  • Aqueous treatment agent, method for producing aqueous treatment agent, and method of using aqueous treatment agent

    WO2019181145A1